Role of self-assembled molecules’ anchoring groups for surface defect passivation and dipole modulation in inverted perovskite solar cells - Wang, Xiaoyu; Faizan, Muhammad; Zhou, Kun; Wang, Xinjiang; Fu, Yuhao; Zhang, Lijun (Chinese physics B, 2024)
Inverted perovskite solar cells have gained prominence in industrial advancement due to their easy fabrication, low hysteresis effects, and high stability. Despite these advantages, their efficiency is currently limited by excessive defects and poor carrier transport at the perovskite–electrode interface, particularly at the buried interface between the perovskite and transparent conductive oxide (TCO). Recent efforts in the perovskite community have focused on designing novel self-assembled molecules (SAMs) to improve the quality of the buried interface. However, a notable gap remains in understanding the regulation of atomic-scale interfacial properties of SAMs between the perovskite and TCO interfaces. This understanding is crucial, particularly in terms of identifying chemically active anchoring groups. In this study, we used the star SAM ([2-(9H-carbazol-9-yl)ethyl] phosphonic acid) as the base structure to investigate the defect passivation effects of eight common anchoring groups at the perovskite–TCO interface. Our findings indicate that the phosphonic and boric acid groups exhibit notable advantages. These groups fulfill three key criteria: they provide the greatest potential for defect passivation, exhibit stable adsorption with defects, and exert significant regulatory effects on interface dipoles. Ionized anchoring groups exhibit enhanced passivation capabilities for defect energy levels due to their superior Lewis base properties, which effectively neutralize local charges near defects. Among various defect types, iodine vacancies are the easiest to passivate, whereas iodine-substituted lead defects are the most challenging to passivate. Our study provides comprehensive theoretical insights and inspiration for the design of anchoring groups in SAMs, contributing to the ongoing development of more efficient inverted perovskite solar cells.